O papel do judiciário na defesa do Patrimônio cultural - Ribas, Giovanna Paola Primor (2009)
Contemporary Law is characterized by the passage of the Constitution to the center of the legal system. The effectiveness of constitutional rules requires a resizing of the role of the judiciary that has faced the paradox of a Constitution rich in rights and of practices that deny the application of such rights. The judiciary ceases to act as a mere mechanical applicator of pre-established rules and assume, with the advent of neoconstitutionalism, the responsibility for the realization of social rights as the right to preservation of the cultural environment. The Brazilian legislation in terms of cultural environment, established several instruments of protection, among them the act of falling. This is a declaratory and discretionary act. Declaratory because a good is not cultural for being registered land, but because of its intrinsic qualities. Discretionary since there is no current risk that threatens the good. It is been inquired if the judiciary can exercise control of an administrative act when the Administration is been omitted from the practice of an act or is acting contrarily to public interest. The demolition of the Adriatic brewery, at the city of Ponta Grossa, Paraná, was an example of the omission of public administration. The case was the object of the lawsuit, which was rejected because the judge understood that the judiciary is not a legitimate entity in a Social Democratic State of Law to recognize a good as cultural. This is only possible an attribution of the executive. This research aims to discuss the possibility of the judiciary, currently and in Brazil, to declare a good as cultural heritage, re-evaluating the principle of separation of powers and the function of the Judiciary related to its social responsibilities. By the perspective of the phenomenon of neoconstitutionalism, the decision of the judiciary was confronted with the historical importance of the good that is been studied and was found a glaring inconsistency between the legal-constitutional system and the actuation of the judiciary in the State of Paraná.